Improving patient knowledge on rational use of antibiotics using educational videos - Muhammad Thesa Ghozali; Bagus Hidayaturrohim; Izdihar Dinah Amalia Islamy (International Journal of Public Health Science (IJPHS), 2023)
Providing proper knowledge on the rational use of antibiotics plays a role in the success of the treatment process of infectious diseases and the prevention of antibiotic resistance. In this modern digital era, healthcare professionals can utilize video as a medium for patient education. This study was meant to determine the efficacy of a video-based educational intervention in improving the levels of knowledge on the rational use of antibiotics. The study used a quasi-experimental pretest-posttest with a control group design and involved 140 participants. Data collection utilized a questionnaire that was carried out from July to December 2021 at the Special Region of Yogyakarta, Indonesia. The intervention was conducted for four weeks with a lecture and group discussion using video as educational media. The results of this study found that educational videos significantly improved the levels of knowledge on the rational use of antibiotics, known by an increase in the mean value of the treatment group by 2.590 with a p-value of 0.001, and a difference in the mean value of posttest scores of both groups by 1.900 with a p-value of 0.001. It could be concluded that video could be utilized as an effective medium of patient education, notably the use of antibiotics.